La expresión de la reflexividad en palenquero (2008)
ABSTRACT: This paper presents the results of a recent research on reflexivity in Palenquero. After the analysis of the grammatical expression of this category in this language, and a comparison with the strategies employed by other Creoles, we argue in favor of a kikongo substratic origin for this structure in Palenquero. However, we suggest that the exposed substratic hypothesis does not exclude a convergence with a universalist explanation.